Patient perspective on symptoms of Notalgia paresthetica: subpopulation results from the Neuropathic Itch Patient Survey (NIRVE) - Brian S. Kim; Jennifer A. Mohawk; Sherri So; Joshua Cirulli; Joana Goncalves; Joseph C. Punzalan; Mark Lebwohl (Taylor & Francis Group, 2024)
Background: Notalgia paresthetica (NP) is a form of neuropathic itch characterized by recurrent itch in the mid back. Much about NP remains unclear, especially the patient experience.Objectives: The Neuropathic Itch Patient Survey (NIRVE) was a global, online survey conducted to better characterize the symptom burden of neuropathic itch from the patient perspective.Patients and methods: This report focuses on the symptom burden of the subpopulation of NIRVE participants with a self-reported diagnosis of NP (N = 91). Respondents reported visiting a median of 2 healthcare providers (HCPs) for their symptoms before receiving an accurate diagnosis of NP.Results: The most common cutaneous symptoms ever experienced were itch/pruritus, sensitive skin, painful or raw skin, numbness, and tingling. The symptoms reported by the most respondents as currently being experienced included itch/pruritus, numbness, painful or raw skin, tingling, and burning or hot sensation. Of patients currently experiencing symptoms, numbness and itch/pruritus were ranked as the most intense, followed by tingling, burning or hot sensation, and then painful or raw skin. Most patients consult multiple healthcare providers (HCPs) before receiving a diagnosis for their condition.Conclusion: Itch is overwhelmingly the most prevalent symptom of the condition, although half of patients also report experiencing sensitive skin, painful or raw skin, numbness, or tingling.